Growing and Implementing Student Character Through The Use of Literacy in The Digital Era - Nasution, Kurniani; Salsabilla, Anisah (Journal of General Education Science, 2024)
The development of technology in the world of education creates many conveniences, including increasing abilities and facilitating access to learning, however, if its use is not balanced by the cultivation of character education, this will lead to a decline in the value or absence of students' character values in the 21st century. The aim of this research is to determine the benefits of digital literacy in the growth and development of student character. The research method used is a descriptive-qualitative method with a literature study approach. Data sources are obtained from analysis results and conclusions obtained from journals. The results of the analysis from this research are that in developing students' character in the 21st century, digital literacy plays a very important role because children tend to be more interested in things related to technology, YouTube and other social media can be used by teachers or educators as a forum for channeling the development of character values. . The conclusion of this research is the use of digital literacy, supervision from parents and teachers by providing or limiting digital ethics, so that students avoid negative words.